2018
DOI: 10.3390/md16100352
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Issue of Tetrodotoxin Targeting

Abstract: This review is devoted to the medical application of tetrodotoxin (TTX), a potent non-protein specific blocker of voltage-gated sodium (NaV) channels. The selectivity of action, lack of affinity with the heart muscle NaV channels, and the inability to penetrate the blood–brain barrier make this toxin an attractive candidate for anesthetic and analgesic drug design. The efficacy of TTX was shown in neuropathic, acute and inflammatory pain models. The main emphasis of the review is on studies focused on the impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 93 publications
0
28
0
Order By: Relevance
“…The inflammation induced by the allergy, thermal stimulation and mechanical pain could be inhibited by TTX [21]. The inflammatory pain of rats could be reduced with the systemic administration [22].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation induced by the allergy, thermal stimulation and mechanical pain could be inhibited by TTX [21]. The inflammatory pain of rats could be reduced with the systemic administration [22].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these promissory effects, there are some limitations for the use of TTX in patients, one of them is its toxicity. This may appear as a consequence of its systemic distribution and it can involve the blocking of diaphragmatic nerves ending in respiratory tract paralysis [17]. Even with previous findings, current studies are needed to improve its use in SCI.…”
Section: Tetrodotoxinmentioning
confidence: 97%
“…Tetrodotoxin (TTX) is a low-molecular-weight guanidine neurotoxin that acts as a specific blocker of voltage-gated sodium (NaV) channel [17]. TTX has neuroprotective properties by blocking NaV channels, preventing neuronal death by diminishing depolarization, cellular Na + /Ca +2 exchange, and neuronal glutamate release [18].…”
Section: Tetrodotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…If successful, TTX will be one of a select few peripherally acting analgesics. To date, preclinical studies have shown TTX to be effective at inhibiting neuropathic [13,14] and inflammatory pain [15][16][17]. In patients with moderate to severe pain due to either cancer or chemotherapy-induced neuropathy who failed other treatments, TTX was seen to reduce pain by 30% below baseline levels in some patients [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%